Assessment of Liver Graft Steatosis: Where Do We Stand?. Issue 3 (28th February 2019) - Cesaretti, Manuela; Addeo, Pietro; Schiavo, Luigi; Anty, Rodolphe; Iannelli, Antonio
Abstract : The growing number of patients on waiting lists for liver transplantation and the shortage of organs have forced many centers to adopt extended criteria for graft selection, moving the limit of acceptance for marginal livers. Steatotic grafts that were, in the past, considered strictly unacceptable for transplantation because of the high risk of early nonfunction are now considered as a potential resource for organ implementation. Several methods to diagnose, measure, classify, and stage steatosis exist, but none can be considered qualitatively and quantitatively "the ideal method" to date. Clinical, biological, and imaging data can be very helpful to estimate graft steatosis, but histology still remains the gold standard. There is an increasing need for rapid and reliable tools to assess graft steatosis. Herein, we present a comprehensive review of the approaches that are currently used to quantify steatosis in liver grafts.